Driving Discomfort of MSEW and Inverted T-type Abutments. (2016) - Nam, Moon S.; Do, Jong-Nam; Jung, Jong-Hong; Park, Min-Cheol
Abstract: Many highway bridges have bumps at the bridge approaches and expansion joints, which is a serious problem from the user point of view. Also, most of highway abutments are made to resist the vertical loads and lateral earth pressure, which induces massive abutment sections compared to the bridge pier. In order to solve these problems, a mechanically stabilized earth wall (MSEW) abutment was developed to reduce height differences at the bridge approach and to reduce the abutment section. The MSEW abutment was compared to the conventional inverted T-type abutment with regard to driving comfort using a vehicle dynamic simulation. Based on the .result, the MSEW abutment provides more driving comfort than the inverted T-type abutment.